Onychocryptosis complicated with osteomyelitis – A case report from tertiary wound care center in South India - Kesavan, Rajesh; Sasikumar, Changam Sheela; Gandeban, Anya (Indian Journal of Case Reports, 2020)
Onychocryptosis or in-grown nail is a painful condition caused by the nail plate’s penetration into the soft surrounding tissue. If left untreated, it leads to infection, discharge, and difficulty in walking, seriously impeding the quality of life of the person. We present a case study of 26-year-old male non-diabetic, in-grown toenail involving the right great toe with osteomyelitis and lymphedema in the right leg. Onychectomy was performed to the patient’s right great toe followed by bone curettage to remove the infected bone. The patient was prescribed with analgesics and antibiotics and he was under constant medical follow- up once a week to change the dressing. Consecutive and careful administration revealed that the growth of healthy matrix and lymphedema is significantly under control.